The segregation of transition metals to iron grain boundaries and their effects on cohesion. (1st June 2022) - Mai, Han Lin; Cui, Xiang-Yuan; Scheiber, Daniel; Romaner, Lorenz; Ringer, Simon P.
Graphical abstract: Abstract: The segregation of transition metal elements to grain boundaries in steels plays a critical role in determining their cohesion. Here, we investigate the segregation, co-segregation, and cohesion effects of various transition metals (Co, Cr, Cu, Mn, Mo, Ni, Nb, Ti, V and W) to different grain boundary characters in ferritic-iron ( α -Fe) through a systematic, brute-force style configurational analysis utilising density functional theory calculations. We demonstrate that differing grain boundary characters change not only transition metal segregation and co-segregation behaviours, but also their effects on cohesion. The effects of co-segregated solutes on cohesion can be substantially different from their summed individual parts. We show that solute-solute interactions at grain boundaries vary significantly as a function of grain boundary character. These interactions are shown to be substantially different from those that occur in the bulk. We introduce a novel quantitative method for assessing effects of segregated elements on interfacial cohesion through calculating the strength of bonds at a grain boundary in the DDEC6 bond-order framework. It is shown that work of separation quantities calculated through rigid separation of surfaces better captures the strength of bonding in most cases, and thus more accurately depicts intergranular fracture. Collectively, these results offer valuable insight towards rational grain boundary engineering in steels.